The Effectiveness of Health Promotion Media Through Booklets and Videos on Increasing Knowledge and Attitudes - Laily Khairiyati; Muhammad Hashfi Abdurrahman; Meiska Fajriani Safitri; Novia Nanda (Lambung Mangkurat University, 2022)
Water is an element that can transmit disease, so clean water treatment is important for the community. This study aimed to determine the effectiveness of health promotion through videos and booklets on increasing public knowledge and attitudes about clean water treatment. This research used experimental research with One Group Pretest Posttest design. The population is the people of Simpang Warga Luar Village RT 01, Aluh-Aluh District, Banjar Regency. The sampling technique used the purposive sampling method with 15 people as the number of samples. Data analysis used the Wilcoxon test. The results showed that the pre-test value of knowledge was 87% in the good category and 13% in the fair category. The post-test results of knowledge are 100% in the good category so there is an increase of 13% in the respondent's knowledge. Based on the results of the attitude pre-test, the results were 46.4% in the good category, 26.8% in the fair category, and 26.8% in the poor category. The results of the attitude post-test were 100% in the good category, so there was an increase of 53.6% in the attitude of the respondents. In this study, it can be concluded that the media through booklets and videos proved to be effective in increasing the knowledge and attitude community about clean water.